Arsenic and old lace [videorecording (DVD)] - Epstein, Julius J., 1909-2000; Epstein, Philip G.; Grant, Cary, 1904-1986; Lane, Priscilla, 1917-1995; Massey, Raymond; Carson, Jack, 1910-1963; Horton, Edward Everett; Lorre, Peter; Gleason, James, 1886-1959; Hull, Josephine, 1877-1957; Adair, Jean, 1873-1953; Alexander, John, 1897-1982; et al. (Criterion collection, 2022)
Frank Capra adapted a hit stage play for this marvelous screwball meeting of the madcap and the macabre. On Halloween, newly married drama critic Mortimer Brewster returns home to Brooklyn, where his adorably dotty aunts greet him with love, sweetness...and a grisly surprise: the corpses buried in their cellar. A bugle-playing brother who thinks he's Teddy Roosevelt, a crazed criminal who's a dead ringer for Boris Karloff, and a seriously slippery plastic surgeon are among the outré oddballs populating Arsenic and Old Lace, a diabolical delight that only gets funnier as the body count rises.